The Effect of Information and Communication Technology in Panama SMEs Performance - Juan Ernesto Mojica Peñalba, Elisa González de Mojica Gonzalo Maldonado Guzman (International Journal of Scientific Research and Management (IJSRM), 2017)
This century is mainly characterized by uncertainty in business, a global market and a high level of competitiveness, in which most businesses must change their business strategies to survive, or adapt to market demands in this sense, the information and communication technology are considered in the literature as one of the strategies that companies can use, not just to stay in the current market, but also to significantly improve their business performance. Thus, the objective of this study is to analyze the existing effects between information and communication technology in business performance, using a sample of 615 micro, small and medium enterprises in panama. The results show that the information and communication technologies have significant positive effects on the business performance of organizations